Overlap Syndrome in a 13- Year- Old Girl: A Case Report - Islam, Mohammad Shahidul; Kabir, Ahmedul; Das, Aparna; Tabassum, Humayara; Joarder, Zabid-Ul Kadir; Hoque, Md. Akramul; Masud, Mohammad Shahin (Journal of Medicine, 2014)
The Overlap Syndrome is a rare condition which comprises two or more connective tissue disease in a same patient. Among them, some are associated with specific autoantibody profile and some are not. Here, we reported a case of overlap syndrome who presented with seizures and features of systemic lupus erythematosus, systemic sclerosis with the presence of strongly positive ANA, Anti snRNP, Anti Scl-70 antibody and weakly positive Anti Sm antibody. DOI: http://dx.doi.org/10.3329/jom.v14i2.19694 J Medicine 2013, 14(2): 218-221